BEYOND READINESS: PERCEPTIONS OF WOMEN OF REPRODUCTIVE AGE (WUS) IN PREGNANCY PLANNING - Deviyanti, Luckyana; Purnamawati, Dewi (Jurnal Mitra Kesehatan, 2026)
Introduction: Pregnancy planning is a crucial process for women of reproductive age (WUS), involving not only physical and financial readiness but also mental preparedness and reproductive knowledge. However, gaps remain between subjective readiness and effective pregnancy planning practices. Method: This study aims to explore the perceptions of women of reproductive age in interpreting pregnancy readiness and planning. This study employed a qualitative approach with a phenomenological design. Data collection was conducted through in-depth interviews with five women of reproductive age as key informants, all of whom were undergoing a natural pregnancy program, and one midwife as a supporting informant at the Cata Medical Clinic. The data were analyzed using thematic analysis. Source triangulation was applied to ensure data validity. Result: The findings indicate that pregnancy readiness is perceived as a balance of mental, emotional, and spiritual well-being. Although most informants felt mentally prepared, there were still significant knowledge gaps regarding ovulation, identifying the fertile window, and the impact of age on fertility. Partner involvement and midwifery counseling were found to play a vital role in supporting more effective pregnancy planning. Conclusion: Optimal pregnancy planning requires a holistic approach that integrates psychological readiness, reproductive knowledge, partner involvement, and professional healthcare guidance.